FXYD5/Dysadherin, a Biomarker of Endometrial Cancer Myometrial Invasion and Aggressiveness: Its Relationship With TGF-β1 and NF-κB Pathways - Besso, María José; Rosso, Marina; Lapyckyj, Lara; Moiola, Cristian Pablo; Matos, María Laura; Mercogliano, María Florencia; Schillaci, Roxana; Reventos, Jaume; Colas, Eva; Gil-Moreno, Antonio; Wernicke, Alejandra; Orti, Roberto; et al. (Frontiers in Oncology, 2019)
Objective: Endometrial cancer (EC) is the second most common gynecological cancer worldwide. Myometrial invasion (MI) is a key event in EC dissemination. This study aimed to evaluate FXYD5/Dys expression in EC tissue and uterine aspirate (UA) biopsies, and to assess molecular/functional changes associated with its expression in cellular models. Methods: FXYD5/Dys mRNA levels were determined in EC tissue and UA biopsies. FXYD5/Dys expression was evaluated in EC RNAseq data from TCGA and GENEVESTIGATOR tools. FXYD5/Dys impact upon E-cadherin expression and cell behavior was assessed in EC Hec1a cells treated with TGF-β1, stably transfected with ETV5, and transiently transfected with FXYD5/Dys siRNA or pcDNA3-FXYD5/Dys. Results: FXYD5/Dys was associated with EC aggressiveness, finding high mRNA levels in tumors depicting MI>50%, grade 3 tumors, and intermediate/high risk of recurrence. FXYD5/Dys was highly expressed at the tumor invasive front compared to the superficial area. Most results were recapitulated in UA biopsies. FXYD5/Dys modulation in Hec1a cells altered cell migration/adhesion and E-cadherin expression. TGF-β1 treatment of Hec1a cells induced FXYD5/Dys expression. TCGA-UCEC RNAseq analysis revealed a positive correlation between FXYD5/Dys, TGF-β1 and PAI-1 mRNA levels. FXYD5/Dys induced NF-kB pathway activation in Hec1a cells. FXYD5/Dys mRNA levels positively correlated with transcriptional activation of NF-kB-p65-regulated genes. Survival analysis revealed patient segregation into Low and High-risk groups, the latter depicting highest FXYD5/Dys, PAI-1, TNF-α and TGF-β1 mRNA levels and shorter survival rates. Conclusion: FXDY5/Dys is a novel biomarker of EC progression related to TGF-β1 and NF-kB pathways that collectively promote tumor dissemination and result in poor patient prognosis.